A demographic approach to assess elevated blood pressure and obesity in prepubescent children: the ExAMIN Youth South Africa study. Issue 11 (November 2021) - Kruger, Ruan; Kruger, Herculina Salomé; Monyeki, Makama Andries; Pienaar, Anita Elizabeth; Roux, Shani Botha-Le; Gafane-Matemane, Lebo Francina; Smith, Wayne; Mels, Catharina Martha Cornelia; Lammertyn, Leandi; Brits, Johanna Susanna; Hanssen, Henner
Abstract : Background: Obesity and hypertension prevalence among children are a concern, with limited evidence available on sex and ethnic differences in childhood blood pressure. We aimed to determine the number of children with hypertension and obesity to identify unique adiposity and blood pressure characteristics by sex and ethnicity, and to estimate the odds of having elevated blood pressure with increasing adiposity. Methods: We included 1062 healthy children (5–9 years of age) in an observational school-based study in South Africa. Pediatric validated automated devices were used to measure brachial blood pressure and performed pulse wave analysis to assess central hemodynamics. Standard anthropometry was carried out to determine body composition and demographic questionnaires were completed. Results: Almost 20% of children were overweight/obese and 14.1% had elevated blood pressure or hypertension (22.8%). Ethnic differences included greater adiposity in white compared with black children (all P < 0.0001), but higher DBP and total vascular resistance in black compared with white children (both P < 0.05). DBP and total vascular resistance were also higher in girls than boys (both P < 0.01). A 51–60% increased risk of developing elevated blood pressure was observed for 1SD (standard deviation) increase of sex-specific BMI [1.60 (1.4–1.8); P < 0.0001] and waist/height ratio [1.51 (1.3–1.7); P < 0.0001]. Conclusion: Unique sex and ethnic differences in body composition and blood pressure exist in prepubescent children, with overweight/obesity increasing the risk of elevated blood pressure. Our findings support primary prevention strategies to combat the growing burden of hypertension and obesity-related diseases in youth. Trial registration: The study is registered on ClinicalTrials.gov (NCT04056377). Abstract : Supplemental Digital Content is available in the text